2019
DOI: 10.1002/jcla.23080
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of circRNA hsa_circ_0067582 in human gastric cancer and its potential diagnostic values

Abstract: Background Gastric cancer (GC) is one of the global mortality diseases and has a poor prognosis due to the lack of ideal tumor biomarkers. Circular RNAs (circRNAs) are an abundant kind of endogenous RNAs that recently are found play a crucial role in the cancer occurrence and development. Nevertheless, little is known with regard to the diagnostic values of these circRNAs for GC. In this article of research, we investigated the role of hsa_circ_0067582 in clinical diagnosis of GC. Materials and Methods We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…The roles of circRNAs in cancer biology have attracted wide attention 16 . Recent studies have demonstrated that some circRNAs are abnormally expressed in GC and involved in the development and progression of GC 17‐20 . CircNRIP1 promotes GC progression by sponging miR‐149‐5p and regulating the AKT1/mTOR pathway 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of circRNAs in cancer biology have attracted wide attention 16 . Recent studies have demonstrated that some circRNAs are abnormally expressed in GC and involved in the development and progression of GC 17‐20 . CircNRIP1 promotes GC progression by sponging miR‐149‐5p and regulating the AKT1/mTOR pathway 17 .…”
Section: Discussionmentioning
confidence: 99%
“…CircFAT1(e2) prevents the development of GC by targeting miR‐548g in the cytoplasm and interacting with the YBX1 protein in the nucleus 18 . The expression level of hsa_circ_0067582 is significantly downregulated in GC tissues 19 . Furthermore, hsa_circ_0000419 is lowly expressed in both GC tissues and plasma samples, making it a potential biomarker in GC screening and predictor of patient prognosis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…GC patients with decreased circ_0005556 levels had a shorter OS than those with higher levels . Circ_0067582 was downregulated in GC tissues and is correlated with increased tumor diameter and high CA19-9 (Yu et al, 2020). Circ_0067582 downregulation was associated with a better prognosis after surgery (Yu et al, 2020).…”
Section: Gastric Cancer (Gc)mentioning
confidence: 95%
“…Circ_0067582 was downregulated in GC tissues and is correlated with increased tumor diameter and high CA19-9 (Yu et al, 2020). Circ_0067582 downregulation was associated with a better prognosis after surgery (Yu et al, 2020). Circ_0000467 was overexpressed in GC tissue and plasma and this was correlated with the TNM stage (Lu et al, 2019b).…”
Section: Gastric Cancer (Gc)mentioning
confidence: 99%
“…In recent years, circular RNAs (circRNAs) are very important in the occurrence and development of tumor and expected to become a biomarker and diagnosis target for tumor treatment. [5][6][7] Predecessors have confirmed that circRNAs are associated with the occurrence, development, and drug resistance of human diseases, such as Alzheimer's disease, hepatocellular carcinoma, lung cancer, breast cancer, and PC. [8][9][10][11][12] Previous studies have shown that circHIPK3 spongs miR-145-5p, miR-124, miR-558, miR-637, miR-193a, miR-338-3p, and miR-637 to regulate oxaliplatin-resistance, proliferation, tube formation, invasion, autophagy, migration, and apoptosis in lung cancer, preeclampsia, gastric cancer, colorectal cancer, chronic myeloid leukemia, bladder cancer, prostate cancer.…”
Section: Introductionmentioning
confidence: 98%